Anticaries material for dental use
Patent Information
- Application Number
- CN202310837830.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-15
- Filing Date
- 2023-07-10
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-07-10
AI Technical Summary
然而,它不具有抗菌效果
[0006]本发明的实施例提供了具有抗菌性质并可以抑制可以引起龋齿的微生物生长的NGIC材料。在某些实施例中,抗菌性质可以从银纳米颗粒或纳米银生物活性玻璃获得或通过其增强。所述NGIC材料的实施例还释放某些离子,这些离子可以使龋齿结构硬化。所提供的牙科材料的实施例对牙齿结构具有良好的粘附性质,使其可以在牙齿的内部结构与材料之间形成紧密的密封。这些性质可以减少龋齿的发生或抑制龋齿。与相关技术的玻璃离子水门汀相比,实施例增强了防龋性质、机械性质和粘接性质。
Smart Images

Figure CN117426986B_ABST
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims the benefit of U.S. Provisional Application Serial No. 63 / 368,562, filed July 15, 2022, the entire contents of which, including any tables, figures or drawings, are hereby incorporated by reference. Background Technology
[0003] Conventional glass polyacrylate or glass ionomer cement (GIC) has occupied a very important position in dentistry since its introduction, mainly as a bonding, sealing and restorative material. Conventional GIC was introduced by Wilson and Kent (1969), which consists of powdered and liquid calcium fluoroaluminate glass powder and an aqueous solution of acrylic polymer [1].
[0004] Conventional GIC has several advantages, such as releasing fluoride ions to prevent or inhibit tooth decay, having ideal transparency during curing, and having a coefficient of thermal expansion similar to that of dentin[2]. However, it does not have antibacterial effects. Its poor physical and mechanical properties, easy dehydration, and moisture contamination also limit its clinical application and lifespan[3]. Summary of the Invention
[0005] Embodiments of the present invention provide a dental material that can be used to manage cavities (e.g., dental caries). Embodiments provide a restorative material for filling cavities, a cement material for bonding other dental restorations to teeth, or a sealant for sealing grooves in the tooth surface to prevent or inhibit caries, and other applications. Embodiments also provide a glass ionomer-based dental material, namely a glass ionomer cement (NGIC).
[0006] Embodiments of the present invention provide NGIC materials with antibacterial properties that can inhibit the growth of microorganisms that can cause tooth decay. In some embodiments, the antibacterial properties may be obtained from or enhanced by silver nanoparticles or nanosilver bioactive glass. Embodiments of the NGIC materials also release certain ions that can harden carious tooth structures. The provided dental materials exhibit good adhesion properties to tooth structures, allowing them to form a tight seal between the material and the internal structure of the tooth. These properties can reduce or inhibit the occurrence of tooth decay. Compared to glass ionomer cements of the related art, the embodiments enhance anti-caries properties, mechanical properties, and adhesive properties.
[0007] Embodiments of the present invention provide NGIC materials for a variety of dental applications (e.g., for caries management and filling or sealing cavities). Embodiments can be used on teeth with cavities to restore the morphology and function of tooth structures with cavities, or to adhere other types of restorations to the tooth surface. Embodiments can also be used in healthy teeth to prevent, reduce, or inhibit caries. Embodiments providing the applied material in the oral cavity can serve as a sustainable release system to release factors for preventing, reducing, or inhibiting caries on part or all of the dentition.
[0008] Examples provide silver nanoparticles as a broad-spectrum antibacterial agent that can inhibit caries and enhance remineralization. Examples also provide bioactive glass (e.g., 45S5 bioactive glass) that exhibits excellent biocompatibility and can be used as a clinical filling material due to its remineralization ability on tooth hard tissues. The provided nanosilver bioactive glass can improve caries inhibition, reduce mineral loss, and promote remineralization of demineralized enamel and dentin, reducing or inhibiting caries around restorations and decreasing the frequency of restoration replacement.
[0009] Some embodiments offer improvements over related technological products such as conventional glass ionomer cement (GIC). Conventional GIC lacks antibacterial properties and cannot prevent or inhibit tooth decay. Conventional GIC also has poor physical properties, exhibiting low fracture resistance, susceptibility to occlusal load fracture, poor wear resistance, and easy wear with daily brushing. For at least these reasons, the lifespan of conventional GIC after placement in the oral cavity is unsatisfactory.
[0010] Embodiments of the present invention provide an antibacterial glass ionomer cement (NGIC) material, which has antibacterial properties, anti-caries function, improved mechanical properties, and improved adhesion to tooth surfaces. These properties increase the duration of restorations in the oral cavity and reduce the frequency of restoration replacement.
[0011] Examples of NGIC provide nanosilver bioactive glass and PVPA with biocompatibility, antibacterial properties, and remineralization properties. Examples containing PVPA also improve the mechanical and adhesive properties of the material. Compared to related art materials, some embodiments significantly improve the antibacterial, remineralization, mechanical, and adhesive properties of the provided NGIC materials.
[0012] The embodiments advantageously provide an NGIC that: provides an alternative restorative material for the phase-out dental amalgam; has improved mechanical properties compared to conventional GIC products; has improved adhesive properties compared to conventional GIC products; provides adequate biocompatibility; can release ions to promote tooth remineralization, thereby inhibiting or preventing tooth decay; can inhibit bacterial growth, thereby inhibiting or preventing tooth decay; and provides increased retention time and reduced replacement frequency in the oral cavity. Attached Figure Description
[0013] Figure 1 This is a graph showing the cell viability of human gingival fibroblasts (HGF), illustrating the effect of materials according to certain embodiments of the invention on the toxicity of HGF. CCK-8 results show the viability of each group over 7 days. The PVPA group had the same biocompatibility as the commercial GIC material in Group B (e.g., conventional GIC without PVPA, also referred to as 0% PVPA).
[0014] Figure 2 Two graphs showing compressive strength and radial tensile strength for NGIC and GIC comparisons are provided, illustrating the results of compressive strength and radial tensile strength in each group according to certain embodiments of the invention. Graph A shows the compressive strength. Graph B shows the radial tensile strength. (*p<0.05, ***p<0.001).
[0015] Figure 3 SEM images and EDX spectra of nano-silver bioactive glass (NanoAg BAG) according to embodiments of the present invention are shown. (A) A 2000x magnified view of NanoAg BAG according to an embodiment of the present invention, showing granular particles; (B) A 6000x magnified view of NanoAg BAG according to an embodiment of the present invention; (C) A 10000x magnified view of NanoAg BAG according to an embodiment of the present invention; (D) EDX spectrum of NanoAg BAG according to an embodiment of the present invention. Figure 3 The SEM images show NanoAg BAG granular particles, and the EDX spectrum of NanoAg BAG shows the peak value of Ag at approximately 3 keV.
[0016] Figure 4 This is a graph showing the cell viability of human gingival fibroblasts (HGF), illustrating the effect of materials according to certain embodiments of the invention on the toxicity of HGF. CCK-8 results show the viability of each group over 7 days (**p<0.01, ns p>0.05).
[0017] Figure 5Two graphs are included, showing the results of compressive strength and radial tensile strength in various material groups according to certain embodiments of the invention. A. Compressive strength. B. Radial tensile strength. (**p<0.01).
[0018] Figure 6 This is a graph showing the fluoride ion release over 14 days of NGIC materials containing NanoAg BAG and PVPA and a conventional GIC control group according to certain embodiments of the present invention.
[0019] Figure 7 This is a graph showing the phosphate ion release over 14 days between NGIC materials containing NanoAg BAG and PVPA and a conventional GIC control group according to certain embodiments of the present invention (**p<0.01).
[0020] Figure 8 This is a graph showing the calcium ion release over 14 days in NGIC materials containing NanoAg BAG and PVPA and a control group according to certain embodiments of the present invention (**p<0.01).
[0021] Figure 9 This is a graph showing the silver ion release of conventional GICs and NGICs containing NanoAg BAG and PVPA over 14 days according to certain embodiments of the present invention (**p<0.01).
[0022] Figure 10 Results of flexural strength in various material groups according to certain embodiments of the present invention are shown. (*p<0.01).
[0023] Figure 11 This is a graph of biomembrane metabolic activity, which shows the antibacterial effect of NGIC in various material groups according to certain embodiments of the present invention. Detailed Implementation
[0024] The NGIC composition according to embodiments of the present invention comprises powder and liquid components. In some embodiments, the NGIC sample is prepared by manually mixing NGIC powder and NGIC liquid. The powder may contain nano-silver bioactive glass and / or silicate glass powder (e.g., calcium aluminum fluorosilicate glass). The liquid may contain poly(vinylphosphonic acid) (PVPA) and / or polyacrylic acid. The liquid may be made from powdered components added to a liquid matrix prior to powder and liquid mixing. The corresponding weight percentage of each component may be adjusted based on the clinical application of NGIC. Different formulations of powder and liquid elements may be used for different clinical situations.
[0025] Table 1. Exemplary components of NGIC
[0026]
[0027] Poly(vinylphosphonic acid) (PVPA) and its derivatives have phosphonic acid bifunctional groups that can form strong associations with cations. PVPA is biocompatible. PVPA-modified surfaces enhance the adhesion, differentiation and mineralization of clonal osteoprogenitor cells [4].
[0028] Examples advantageously use PVPA to replace some or all of the relevant technical polymer materials, such as polyacrylic acid, poly(acrylic acid-itaconic acid), and poly(acrylic acid-co-maleic acid) in conventional GIC formulations [5]. In some embodiments, the substitutes improve mechanical properties compared to conventional GIC compositions of the relevant art.
[0029] Silver nanoparticles, including silver nanoparticles, are broad-spectrum antibacterial agents that can be used to prevent, reduce or inhibit dental caries[6]. Silver nanoparticles are particles of silver atoms aggregated together to form a size of 1-100 nm (e.g., particle size of 8-15 nm). Due to their high surface area, they can attach to the outer cell membrane of bacteria, thereby altering bacterial permeability and cell structure to kill bacterial cells[7].
[0030] Bioactive glass (e.g., 45S5) It has excellent biocompatibility [8]. 45S5 It promotes the remineralization of the hard tissues of the tooth, including enamel and dentin[9]. Glass particles also have antibacterial properties
[10] .
[0031] Embodiments of the present invention offer numerous advantages over related technologies. For example, U.S. Patent 5,179,135 (Ellis et al.) teaches a poly(vinylphosphonic acid) glass ionomer cement, which is a simple mixture of conventional glass ionomer cement material with a poly(vinylphosphonic acid) solution and silicate glass powder. Embodiments of the present invention advantageously use poly(vinylphosphonic acid) (PVPA) solids instead of liquids to improve the mechanical strength of the material. Embodiments also incorporate synthetic nanosilver bioactive glass, PVPA solids, and silicate glass powder to provide a composition with a variety of advantageous properties. Silver nanoparticles are broad-spectrum antibacterial agents that can inhibit caries and enhance remineralization, while 45S5 bioactive glass has good biocompatibility and provides a clinical filling material due to its ability to provide remineralization to tooth tissue. Embodiments inhibit caries by releasing fluoride ions more stably over a longer period and reducing mineral loss, and promote remineralization of demineralized enamel and dentin better than conventional GIC materials. The provided nano-silver bioactive glass improves caries inhibition, reduces caries and mineral loss around the restoration, promotes remineralization of demineralized enamel and dentin, and reduces the frequency of restoration replacement.
[0032] Examples provide unique compositions of dental materials comprising a mixture of fluoroaluminosilicate glass powder and a mixture of nano-silver bioactive glass and polyacrylic acid and PVPA solids. The provided compositions are specifically designed to address the pathogenesis of tooth decay and offer multiple benefits such as improved mechanical strength, antibacterial properties, and remineralization properties. Using a mixture of GIC liquid and PVPA solids instead of pure PVPA liquid is a novel approach to significantly improve the mechanical strength of the material. Furthermore, the combination of nano-silver bioactive glass and 45S5 bioactive glass enhances the antibacterial and remineralization properties of the material, making it a highly effective dental material for precise caries management. In some embodiments, the provided compositions offer significant improvements over related technologies and represent an advancement in the field of caries management.
[0033] The embodiments advantageously incorporate synthetic nanosilver bioactive glass into dental materials. The provided silver nanoparticles are broad-spectrum antibacterial agents that can be used to prevent caries and enhance remineralization. Furthermore, 45S5 bioactive glass exhibits good biocompatibility and, due to its ability to remineralize and form tooth hard tissue, can be used as a clinical filling material. Compared to conventional GIC materials, the provided 45S5 bioactive glass can prevent caries by releasing fluoride ions more stably over a longer period, and can reduce mineral loss and promote the remineralization of demineralized enamel and dentin. The application of nanosilver bioactive glass can improve caries prevention, reduce peri-restorative caries, reduce mineral loss, promote the remineralization of demineralized enamel and dentin, and reduce the frequency of restoration replacement.
[0034] Examples provide dental cements with antibacterial properties to minimize new caries caused by bacterial growth. The provided dental cements also promote enamel remineralization. In some embodiments, the antibacterial agent is nanosilver, which is a component of bioactive glass. The bioactive glass may be commercially available 45S5 bioactive glass. The base dental cement is also commercially available, meaning that the present invention can be readily prepared from commercially available materials already approved for use inside the human body. In one embodiment, the composition is a mixture of glass ionomer cement and nanosilver bioactive glass. Such compositions exhibit good compressive, flexural, and radial tensile strength.
[0035] Another example of how embodiments of the present invention provide advantages over related technologies can be seen in U.S. Patent Application 2021 / 0212906 (Sakamoto et al.), which teaches dental glass ionomer cement compositions composed of non-crosslinked polyacrylic acid and silicate glass powder. In contrast, embodiments of the present invention provide nano-silver bioactive glass, silicate glass powder, and polyacrylic acid added together with poly(vinylphosphonic acid) (PVPA). The provided PVPA improves the mechanical strength, fatigue limit, and adhesive properties of the restoration, extends the retention time of the restoration, and reduces the frequency of restoration replacement.
[0036] Another example of how embodiments of the present invention provide advantages over related technologies can be seen in U.S. Patent Application 2007 / 0122356 (Kessler et al.), which teaches an antimicrobial glass composition comprising silver in combination with glass ionomer cement. One difference between the related technologies and embodiments of the present invention is the composition of the materials. While the related technologies disclose a plastic-reinforced glass ionomer cement composite that combines a composite material containing glass ionomers and silver particles; embodiments of the present invention provide glass ionomer cement containing nano-silver bioactive glass and PVPA. Compared to the composite, the prepared glass ionomer cement exhibits superior fluoride ion release performance and therefore better remineralization. Compared to the related technologies, the use of nano-silver bioactive glass and PVPA in embodiments of the present invention can provide improved antimicrobial properties and better overall performance.
[0037] Another example of how embodiments of the present invention provide advantages over related technologies can be seen with regard to U.S. Patent 9,211,246 (Hack), which teaches a bioactive glass containing 0-15% silver oxide with an average particle size of about 10 micrometers.
[0038] Micrometer-sized bioactive glasses are less effective against bacteria than those provided in some embodiments of the present invention, at least in part due to the reduced surface area. The use of large-sized bioactive glasses in related technologies may compromise the mechanical strength of the additive material, making it unsuitable for dental restorations. Furthermore, related technology materials use 0-15% silver oxide. Silver oxide does not provide the same level of antibacterial properties as nano-silver bioactive glasses. Additionally, a high weight percentage of silver oxide can impair the aesthetics of the material, which is an important property of dental restorative materials.
[0039] Bioactive glass and silver have different particle sizes. Embodiments of the present invention provide bioactive glass with a size of 50-120 nm incorporating silver nanoparticles of 8-15 nm in size. Incorporating silver nanoparticles into bioactive glass is beneficial and, in some embodiments, necessary to achieve optimal antimicrobial properties while maintaining the material's mechanical strength and aesthetics.
[0040] In some embodiments, bioactive glass particles with a size of 50-120 nm are important because biomaterials containing nanoparticles exhibit better bioactivity and higher mechanical stability compared to micron-sized bioactive glass particles. Bioactive glass particles larger than 120 nm exhibit slower bioactivity and do not provide good mechanical properties at lower concentrations.
[0041] In some embodiments, silver nanoparticles with a size of 8-15 nm are important because nano-sized particles have a higher surface area than micron-sized particles. They can attach to the outer cell membrane of bacteria, thereby altering bacterial permeability and cell structure to kill the bacterial cells. Silver nanoparticles smaller than 8 nm can exhibit stronger cytotoxicity due to their high surface area. Silver nanoparticles larger than 15 nm are less efficient at inhibiting bacteria.
[0042] Another example of how embodiments of the present invention provide advantages over related technologies can be seen in WIPO application WO 2022 / 058448 (deBarra et al.), which teaches non-nanosilver bioactive glass. Embodiments of the present invention incorporate nanosilver bioactive glass into silicate glass powder, which improves the mechanical and antimicrobial properties of NGIC compared to related technologies that only teach how to improve the solidification (e.g., working) time and flexural strength of GIC.
[0043] Example 10 provides non-limiting and exemplary embodiments of therapeutic compounds for dental use according to embodiments of the present invention.
[0044] In this embodiment, the composition of the nanosilver bioactive glass (NBG) (all percentages by weight) is 41.1% SiO2, 23.9% CaO, 24.0% Na2O, 5.9% P2O5, and 5.1% Ag nanoparticles. NBG exhibits chemical stability in biological environments. It also possesses antibacterial properties because it can locally increase pH and osmotic pressure, thereby creating an environment unfavorable to bacterial growth. Other suitable or alternative values or ranges for the composition include those listed in the following paragraphs, used alone or in various combinations.
[0045] In this composition, 41.1% SiO2 is selected to provide the bioactivity of the NGIC bioactive glass. Higher SiO2 content may decrease bioactivity, while lower SiO2 content may increase bioactivity. Other suitable values or ranges include 43-47%.
[0046] In this composition, 23.9% CaO is chosen to provide the remineralization effect of NGIC because it increases the release of calcium ions. Higher amounts can increase calcium release and remineralization effect. Lower amounts can decrease calcium release and reduce remineralization effect. Other suitable values or ranges include 22.5-26.5%.
[0047] In this composition, 24.0% Na₂O is chosen to provide the antibacterial properties of NGIC by increasing the local pH (which is cytotoxic to bacteria) and to promote or accelerate glass degradation. Higher amounts can increase antibacterial efficacy and glass degradation, but may also increase cytotoxicity. Lower amounts can decrease antibacterial efficacy and glass degradation. Other suitable values or ranges include 22.5-26.5%.
[0048] In this composition, 5.9% P₂O₅ is chosen to provide mineralization according to the Ca:P ratio because it increases phosphate ion release, promoting apatite formation and inducing the crystallization of the calcium phosphate phase. Higher amounts can inhibit bioactivity. Lower amounts can reduce the apatite formation rate. Other suitable values or ranges include 5-7%.
[0049] In this composition, 5.1% Ag nanoparticles are selected to provide the antibacterial effect and biocompatibility of NGIC. Higher amounts may provide better antibacterial effects but may also increase cytotoxicity. Lower amounts may reduce both antibacterial effect and cytotoxicity. Other suitable values or ranges include 5-10%.
[0050] In this composition, Ag nanoparticles with a size range of 8-15 nm are selected to provide better antibacterial efficacy of NGIC. Larger (higher) Ag size can enhance antibacterial efficacy, but may also enhance cytotoxicity. Smaller (lower) Ag size can reduce antibacterial efficacy, but may reduce cytotoxicity.
[0051] In this composition, NBG particles with a size range of 50-120 nm are formed to provide suitable mechanical strength and antibacterial effect. Larger NBG particle sizes can reduce mechanical strength, while smaller NBG particle sizes result in poorer bacterial inhibition.
[0052] In this composition, NBG is mixed with NGIC as described below at a ratio ranging from (1% NBG to (99% NGIC)) to (5% NBG to (95% NGIC)) to provide suitable mechanical strength and antibacterial efficacy for biocompatible NGIC. Higher amounts of NBG can provide better antibacterial efficacy, but with reduced mechanical strength and increased cytotoxicity. Lower amounts of NBG can provide lower antibacterial efficacy and higher mechanical strength, as well as reduced cytotoxicity. Specifically, a ratio of 1% NBG to 99% NGIC was found to provide the highest mechanical strength (e.g., significantly improved compressive and radial tensile strength) and similar biocompatibility to commercially available GICs. A ratio of 2% NBG to 98% NGIC was found to provide lower mechanical strength, increased cytotoxicity (but still higher than the strength of 5% NBG to 95% NGIC), and released more Ag, Ca, and P compared to 1% NBG to 99% NGIC. It was found that a 5% NBG to 95% NGIC ratio provides lower mechanical strength, increased cytotoxicity, and releases more Ag, Ca, and P compared to (1% NBG to 99% NGIC) or (2% NBG to 98% NGIC).
[0053] In this embodiment, the NGIC powder comprises 0.41-2.055 wt% SiO2 (e.g., corresponding to 1-5 wt% bioactive glass), 0.239-1.195 wt% CaO, 0.24-1.2 wt% Na2O, 0.59-0.295 wt% P2O5, 0.51-0.255 wt% Ag nanoparticles, 33.4-41.48 wt% SiO2 (e.g., corresponding to 99-95 wt% GIC powder), 9.09-28.314 wt% Al2O3, 1.52-2.376 wt% AlF3, 14.915-19.899 wt% CaF2, 3.42-9.207 wt% NaF, and 3.61-11.88 wt% AlPO4.
[0054] In this composition, 0.41-2.055 wt% of SiO2 (e.g., SiO2 composition in Ag bioactive glass (i.e., Ag45S5 bioactive glass)) is selected to provide suitable mechanical strength and antibacterial effect for biocompatible NGIC. Higher amounts can provide better antibacterial effect, but with reduced mechanical strength and increased cytotoxicity. Lower amounts can provide lower antibacterial effect, mechanical strength, and reduced cytotoxicity.
[0055] In this composition, 0.239–1.195 wt% CaO is selected to provide suitable mechanical strength and antibacterial efficacy for biocompatible NGIC. Higher amounts can provide better antibacterial efficacy, but with reduced mechanical strength and increased cytotoxicity. Lower amounts can provide lower antibacterial efficacy, mechanical strength, and reduced cytotoxicity.
[0056] In this composition, 0.24-1.2 wt% Na₂O is selected to provide suitable mechanical strength and antibacterial efficacy for biocompatible NGIC. Higher amounts can provide better antibacterial efficacy, but with reduced mechanical strength and increased cytotoxicity. Lower amounts can provide lower antibacterial efficacy, mechanical strength, and reduced cytotoxicity.
[0057] In this composition, 0.59–0.295 wt% P₂O₅ is selected to provide suitable mechanical strength and antibacterial efficacy for biocompatible NGIC. Higher amounts can provide better antibacterial efficacy, but with reduced mechanical strength and increased cytotoxicity. Lower amounts can provide lower antibacterial efficacy, mechanical strength, and reduced cytotoxicity.
[0058] In this composition, 0.51–0.255 wt% of Ag nanoparticles (e.g., added to NGIC as part of Ag-substituted NBG) are selected to provide suitable mechanical strength and antibacterial efficacy for biocompatible NGIC. Higher amounts can provide better antibacterial efficacy, but with reduced mechanical strength and increased cytotoxicity. Lower amounts can provide lower antibacterial efficacy, mechanical strength, and reduced cytotoxicity.
[0059] Select 33.4-41.48 wt% SiO2 to provide SiO4 after the acid-base reaction in NGIC. 4- Release. Higher amounts can increase SiO4 release. 4- The release of SiO4. Lower amounts can reduce the release of SiO4. 4- The release.
[0060] In this composition, 9.09-28.314 wt% Al₂O₃ is selected to provide solidification for cement formation by forming anionic sites in the silica glass network. Higher amounts can increase the release of aluminum ions. Lower amounts can reduce the release of aluminum ions.
[0061] In this composition, 1.52-2.376 wt% AlF3 is selected to provide fluoride ion release after the acid-base reaction in NGIC. Higher amounts can increase fluoride ion release, while lower amounts can decrease it.
[0062] In this composition, 14.915-19.899 wt% CaF2 is selected to provide the release of calcium and fluoride ions during the acid-base reaction of NGIC. Higher amounts can increase the release of calcium and fluoride ions, while lower amounts can decrease the release of calcium and fluoride ions.
[0063] In this composition, 3.42-9.207 wt% NaF is selected to provide the release of sodium and fluoride ions after the acid-base reaction in NGIC. Higher amounts can increase the release of sodium and fluoride ions, while lower amounts can decrease the release of sodium and fluoride ions.
[0064] In this composition, 3.61-11.88 wt% of AlPO4 is selected to provide phosphate ion release after the acid-base reaction in NGIC. Higher amounts can increase phosphate ion release, while lower amounts can decrease it.
[0065] In this embodiment, the NGIC liquid contains 45 wt% deionized water, 36 wt% polyacrylic acid, 9 wt% polycarboxylic acid and 10 wt% poly(vinylphosphonic acid).
[0066] In this composition, 45 wt% deionized water is selected as the solvent to dissolve polyacrylic acid, ionize it, and provide protons, thereby exhibiting a Bronsted-Lowry acid. Higher amounts can accelerate the acid-base reaction of NGIC, while lower amounts can delay it.
[0067] In this composition, 36 wt% polyacrylic acid was chosen to provide higher mechanical strength and a suitable setting time. Higher amounts can reduce the mechanical strength of NGIC. Lower amounts can make NGIC difficult to mix and result in lower mechanical strength.
[0068] In this composition, 9 wt% of a polycarboxylic acid is selected to improve processing properties by extending the working time and shortening the setting time. Higher amounts can increase the working time and reduce the setting time. Lower amounts can reduce the working time and increase the setting time.
[0069] In this composition, 10 wt% of poly(vinylphosphonic acid) was chosen to optimize the mechanical properties of NGIC. Higher amounts would make the GIC liquid and PVPA solid difficult to mix. Lower amounts would not improve mechanical strength.
[0070] The specific structural, measurable, or quantifiable differences between GIC solutions known in the related art and the NGIC solid plus NGIC liquid formulations provided in the embodiments of the present invention include the following: For PVPA, solid-state 31P NMR can detect the PVPA functional group (OH)₂P=O (acid group). The chemical shift is approximately 33 ppm. For Ag, XPS can detect and quantify the amount of Ag in the product.
[0071] Now turn to the attached image. Figure 1 This is a graph illustrating the effect of materials according to certain embodiments of the invention on the optical density (OD) of cell culture medium after treatment with Cell Counting Kit-8 (CCK-8) at 450 nm, where OD represents the number of viable human gingival fibroblasts (HGF) in the culture medium. The Cell Counting Kit-8 (CCK-8) results show the viability of the blank control, 0% PVPA, 1% PVPA, 5% PVPA, 10% PVPA, and 20% PVPA groups at 1, 3, 5, and 7 days. The PVPA groups have the same biocompatibility as commercially available GIC materials (e.g., represented by 0% PVPA).
[0072] Figure 2 Two graphs are included, showing the results of compressive strength and radial tensile strength in the 0%, 1%, 5%, 10%, and 20% PVPA groups according to certain embodiments of the invention. Graph A represents compressive strength, and Graph B represents radial tensile strength. (*p<0.05, ***p<0.001).
[0073] Figure 3 Scanning electron microscope (SEM) images and EDX spectra of NanoAg BAG according to embodiments of the present invention are shown. (A) A 2000x magnified view of NanoAg BAG according to an embodiment of the present invention, showing granular particles; (B) A 6000x magnified view of NanoAg BAG according to an embodiment of the present invention; (C) A 10000x magnified view of NanoAg BAG according to an embodiment of the present invention; (D) The EDX spectrum of NanoAg BAG according to an embodiment of the present invention. The SEM images show the granular particles of NanoAg BAG, and the EDX spectrum of NanoAg BAG shows the peak value of Ag.
[0074] Figure 4This graph illustrates the effect of treatment with Cell Counting Kit-8 (CCK-8) at 450 nm on the optical density (OD) of cell culture medium at days 1, 3, 5, and 7 for blank control, 0% NanoAg BAG + 0% PVPA, 0% NanoAg BAG + 10% PVPA, 1% NanoAg BAG + 10% PVPA, 2% NanoAg BAG + 10% PVPA, and 5% NanoAg BAG + 10% PVPA groups, according to certain embodiments of the present invention. The OD represents the number of viable human gingival fibroblasts (HGFs) in the culture medium. CCK-8 results show the viability of each group at 7 days (**p < 0.01, ns p > 0.05).
[0075] Figure 5 Two graphs are included, showing the results of compressive strength and radial tensile strength in material groups of 0% NanoAg BAG+0% PVPA, 0% NanoAg BAG+10% PVPA, 1% NanoAg BAG+10% PVPA, 2% NanoAg BAG+10% PVPA, and 5% NanoAg BAG+10% PVPA according to certain embodiments of the invention. Graph A represents compressive strength, and Graph B represents radial tensile strength. (**p<0.01).
[0076] Figure 6 This is a graph showing the fluoride ion release over 14 days for NGIC materials containing NanoAg BAG and PVPA in groups of 0% NanoAg BAG+10% PVPA, 1% NanoAg BAG+10% PVPA, 2% NanoAg BAG+10% PVPA, and 5% NanoAg BAG+10% PVPA, and a control group (0% NanoAg BAG+0% PVPA) according to certain embodiments of the present invention.
[0077] Figure 7 This is a graph showing the phosphate ion release on day 7 and day 14 of NGIC materials containing NanoAg BAG and PVPA in groups of 0% NanoAg BAG+10% PVPA, 1% NanoAg BAG+10% PVPA, 2% NanoAg BAG+10% PVPA, and 5% NanoAg BAG+10% PVPA, and a control group (0% NanoAg BAG+0% PVPA) according to certain embodiments of the present invention (**p<0.01).
[0078] Figure 8This is a graph showing the calcium ion release on day 7 and day 14 of NGIC materials containing NanoAg BAG and PVPA in groups of 0% NanoAg BAG+10% PVPA, 1% NanoAg BAG+10% PVPA, 2% NanoAg BAG+10% PVPA and 5% NanoAg BAG+10% PVPA, and a control group (0% NanoAg BAG+0% PVPA) according to certain embodiments of the present invention (**p<0.01).
[0079] Figure 9 This is a graph showing the silver ion release on day 7 and day 14 of conventional GIC (0% NanoAg BAG + 0% PVPA) and NGIC containing NanoAg BAG and PVPA in groups of 0% NanoAg BAG + 10% PVPA, 1% NanoAg BAG + 10% PVPA, 2% NanoAg BAG + 10% PVPA, and 5% NanoAg BAG + 10% PVPA, according to certain embodiments of the present invention (**p<0.01).
[0080] Exemplary embodiments
[0081] The invention can be better understood by referring to certain illustrative examples, which include, but are not limited to, the following:
[0082] Example 1. A glass ionomer cement (NGIC), comprising:
[0083] Silicate glass powder;
[0084] Polyacrylic acid powder;
[0085] Poly(vinylphosphonic acid) (PVPA) powder;
[0086] Nano-silver bioactive glass; and
[0087] Polyacrylic acid solution.
[0088] Example 2. The NGIC according to Example 1, wherein the silicate glass powder comprises calcium aluminum fluoride silicate glass.
[0089] Example 3. The NGIC according to Example 2, wherein the silicate glass powder is calcium aluminum fluoride silicate glass.
[0090] Example 4. NGIC according to Example 1, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 99 / 1.
[0091] Example 5. NGIC according to Example 1, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 95 / 5 but less than or equal to 99 / 1.
[0092] Example 6. NGIC according to Example 1, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 90 / 10 but less than or equal to 95 / 5.
[0093] Example 7. NGIC according to Example 1, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 80 / 20 but less than or equal to 90 / 10.
[0094] Example 8. NGIC according to Example 1, wherein the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 99 / 1.
[0095] Example 9. NGIC according to Example 1, wherein the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 98 / 2 but less than or equal to 99 / 1.
[0096] Example 10. The NGIC according to Example 1, wherein the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 95 / 5 but less than or equal to 98 / 2.
[0097] Example 11. NGIC according to Example 1, wherein the wt% ratio of (polyacrylic acid) / PVPA is about 90 / 10, and the wt% ratio of (silicate glass powder) / (nano silver bioactive glass) is greater than 95 / 5 but less than or equal to 99 / 1.
[0098] Example 12. A therapeutic agent comprising:
[0099] Glass ionomer cement (NGIC), wherein the NGIC comprises the following blends:
[0100] Dry powder, said dry powder comprising silicate glass powder, polyacrylic acid powder, and nano-silver bioactive glass; and
[0101] A solution containing polyacrylic acid and poly(vinylphosphonic acid) (PVPA).
[0102] Example 13. The therapeutic agent according to Example 12, wherein the silicate glass powder comprises calcium aluminum fluorosilicate glass.
[0103] Example 14. The therapeutic agent according to Example 12, wherein the silicate glass powder is calcium aluminum fluorosilicate glass.
[0104] Example 15. The therapeutic agent according to Example 12, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 99 / 1.
[0105] Example 16. The therapeutic agent according to Example 12, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 95 / 5 but less than or equal to 99 / 1.
[0106] Example 17. The therapeutic agent according to Example 12, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 90 / 10 but less than or equal to 95 / 5.
[0107] Example 18. The therapeutic agent according to Example 12, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 80 / 20 but less than or equal to 90 / 10.
[0108] Example 19. The therapeutic agent according to Example 12, wherein the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 99 / 1.
[0109] Example 20. The therapeutic agent according to Example 12, wherein the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 98 / 2 but less than or equal to 99 / 1.
[0110] Example 21. The therapeutic agent according to Example 12, wherein the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 95 / 5 but less than or equal to 98 / 2.
[0111] Example 22. The therapeutic agent according to Example 12, wherein the wt% ratio of (polyacrylic acid) / PVPA is about 90 / 10, and the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 95 / 5 but less than or equal to 99 / 1.
[0112] Example 23. A method for preparing NGIC, the method comprising combining a liquid mixture of polyacrylic acid and PVPA with a powdered mixture of silicate glass powder, polyacrylic acid powder and nano-silver bioactive glass.
[0113] Example 24. The method according to Example 23, wherein the silicate glass powder comprises calcium aluminum fluoride silicate glass.
[0114] Example 25. The method according to Example 23, wherein the silicate glass powder is calcium aluminum fluoride silicate glass.
[0115] Example 26. The method according to Example 23, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 99 / 1.
[0116] Example 27. The method according to Example 23, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 95 / 5 but less than or equal to 99 / 1.
[0117] Example 28. The method according to Example 23, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 90 / 10 but less than or equal to 95 / 5.
[0118] Example 29. The method according to Example 23, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 80 / 20 but less than or equal to 90 / 10.
[0119] Example 30. The method according to Example 23, wherein the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 99 / 1.
[0120] Example 31. The method according to Example 23, wherein the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 98 / 2 but less than or equal to 99 / 1.
[0121] Example 32. The method according to Example 23, wherein the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 95 / 5 but less than or equal to 98 / 2.
[0122] Example 33. The method according to Example 23, wherein the wt% ratio of (polyacrylic acid) / PVPA is about 90 / 10, and the wt% ratio of (silicate glass powder) / (nano silver bioactive glass) is greater than 95 / 5 but less than or equal to 99 / 1.
[0123] Example 34. A method for treating dental caries in a subject, the method comprising:
[0124] Provide a therapeutic agent, said therapeutic agent comprising:
[0125] Glass ionomer cement (NGIC), wherein the NGIC comprises:
[0126] Silicate glass powder;
[0127] Nano-silver bioactive glass;
[0128] Polyacrylic acid powder; and
[0129] Poly(vinylphosphonic acid) (PVPA); and
[0130] The therapeutic agent is applied to at least one surface within the oral cavity of the subject.
[0131] Example 35. The method according to Example 34, wherein the silicate glass powder comprises calcium aluminum fluoride silicate glass.
[0132] Example 36. The method according to Example 34, wherein the silicate glass powder is calcium aluminum fluorosilicate glass.
[0133] Example 37. The method according to Example 34, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 99 / 1.
[0134] Example 38. The method according to Example 34, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 95 / 5 but less than or equal to 99 / 1.
[0135] Example 39. The method according to Example 34, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 90 / 10 but less than or equal to 95 / 5.
[0136] Example 40. The method according to Example 34, wherein the wt% ratio of (polyacrylic acid) / PVPA is greater than 80 / 20 but less than or equal to 90 / 10.
[0137] Example 41. The method according to Example 34, wherein the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 99 / 1.
[0138] Example 42. The method according to Example 34, wherein the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 98 / 2 but less than or equal to 99 / 1.
[0139] Example 43. The method according to Example 34, wherein the wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than 95 / 5 but less than or equal to 98 / 2.
[0140] Example 44. The method according to Example 34, wherein the wt% ratio of (polyacrylic acid) / PVPA is about 90 / 10, and the wt% ratio of (silicate glass powder) / (nano silver bioactive glass) is greater than 95 / 5 but less than or equal to 99 / 1.
[0141] Example 45. The method according to Example 34, wherein the therapeutic agent further comprises a second solvent, a thickener, a buffer solution, and / or an oil.
[0142] Example 46. The method according to Example 34, wherein the application includes rinsing, spraying, brushing, injection or any combination thereof.
[0143] Example 47. The method according to Example 34, further comprising crosslinking, wherein the therapeutic agent further comprises an oil, the oil comprising at least one component having crosslinking functionality and optionally comprising a crosslinking agent.
[0144] Example 48. A nano-silver bioactive glass, comprising:
[0145] Approximately 41% SiO2;
[0146] Approximately 24% CaO;
[0147] Approximately 24% Na₂O;
[0148] Approximately 6% P2O5, and
[0149] Approximately 5% Ag nanoparticles.
[0150] Example 49. A nano-silver bioactive glass, comprising:
[0151] 41% SiO2,
[0152] 24% CaO
[0153] 24% Na2O,
[0154] 6% P2O5, and
[0155] 5% Ag nanoparticles.
[0156] Example 50. A nano-silver bioactive glass, comprising:
[0157] Approximately 41.1% SiO2;
[0158] Approximately 23.9% CaO;
[0159] Approximately 24.0% Na₂O
[0160] Approximately 5.9% P2O5 and approximately 5.1% Ag nanoparticles.
[0161] Example 51. A nano-silver bioactive glass, comprising:
[0162] 41.1% SiO2
[0163] 23.9% CaO
[0164] 24.0% Na2O
[0165] 5.9% P2O5, and
[0166] 5.1% Ag nanoparticles.
[0167] Example 52. A therapeutic agent comprising:
[0168] Glass ionomer cement (NGIC), wherein the NGIC comprises the following blends:
[0169] The dry powder comprises 0.51-0.255 wt% Ag nanoparticles.
[0170] and at least two of the following:
[0171] 0.41-2.055 wt% of SiO2,
[0172] 0.239-1.195 wt% of CaO,
[0173] 0.24-1.2 wt% of Na₂O,
[0174] 0.59-0.295 wt% of P2O5,
[0175] 33.4-41.48 wt% SiO2,
[0176] Al2O3 in amounts of 19.09-28.314 wt%.
[0177] 1.52-2.376 wt% of AlF3,
[0178] 14.915-19.899 wt% of CaF2,
[0179] 3.42-9.207 wt% of NaF, and
[0180] 3.61-11.88 wt% of AlPO4; and
[0181] The solution contains about 36 wt% polyacrylic acid and about 10 wt% poly(vinylphosphonic acid) (PVPA).
[0182] Example 53. A therapeutic agent comprising:
[0183] Glass ionomer cement (NGIC), wherein the NGIC comprises the following blends:
[0184] Dry powder, the dry powder comprising:
[0185] Ag nanoparticles in amounts of 0.51-0.255 wt%.
[0186] 0-2.055 wt% of SiO2,
[0187] 0-1.195 wt% of CaO,
[0188] 0-1.2 wt% of Na₂O,
[0189] 0-0.295wt% of P2O5,
[0190] 33.4-41.48 wt% SiO2,
[0191] 0-28.314 wt% of Al2O3
[0192] 0-2.376 wt% of AlF3,
[0193] 14.915-19.899 wt% of CaF2,
[0194] 3.42-9.207 wt% of NaF, and
[0195] 0-11.88 wt% of AlPO4; and
[0196] The solution comprises:
[0197] 45wt% H2O,
[0198] 36wt% polyacrylic acid
[0199] 9wt% polycarboxylic acids, and
[0200] 10wt% Poly(vinylphosphonic acid) (PVPA).
[0201] Example 54. A therapeutic agent comprising:
[0202] A novel glass ionomer cement (NGIC), the NGIC comprising the following blend: a dry powder comprising:
[0203] Ag nanoparticles in amounts of 0.51-0.255 wt%.
[0204] 0.41-2.055 wt% of SiO2,
[0205] 0.239-1.195 wt% of CaO,
[0206] 0.24-1.2 wt% of Na₂O,
[0207] 0.59-0.295 wt% of P2O5,
[0208] 33.4-41.48 wt% SiO2,
[0209] Al2O3 in amounts of 19.09-28.314 wt%.
[0210] 1.52-2.376 wt% of AlF3,
[0211] 14.915-19.899 wt% of CaF2,
[0212] 3.42-9.207 wt% of NaF, and
[0213] 3.61-11.88 wt% of AlPO4; and
[0214] The solution comprises:
[0215] 45wt% H2O,
[0216] 36wt% polyacrylic acid
[0217] 9wt% polycarboxylic acids, and
[0218] 10wt% Poly(vinylphosphonic acid) (PVPA).
[0219] Example 55. A therapeutic agent comprising a mixture of the following:
[0220] Polyacrylic acid liquid;
[0221] Poly(vinylphosphonic acid) (PVPA) solids;
[0222] Nano-silver bioactive glass (NBG); and
[0223] Silicate glass powder.
[0224] Example 56. The therapeutic agent according to Example 55, wherein the nanosilver bioactive glass comprises nanosilver particles with a size of 8-15 nm.
[0225] Example 57. The therapeutic agent according to Example 55, wherein the nanosilver bioactive glass comprises a group of nanosilver particles, most of which are between 8-15 nm in size.
[0226] Example 58. The therapeutic agent according to Example 55, wherein the nanosilver bioactive glass comprises a group of nanosilver particles, wherein 90% of the nanosilver particles are between 8-15 nm in size.
[0227] Example 59. The therapeutic agent according to Example 55, wherein the nanosilver bioactive glass comprises a group of nanosilver particles, wherein 99% of the nanosilver particles are between 8-15 nm in size.
[0228] Example 60. The therapeutic agent according to Example 55, wherein the nanosilver bioactive glass comprises a group of nanosilver particles consisting essentially of nanosilver particles with a size of 8-15 nm.
[0229] Example 61. The therapeutic agent according to Example 55, wherein the nanosilver bioactive glass comprises a group of nanosilver particles consisting of nanosilver particles with a size of 8-15 nm.
[0230] Example 62. The therapeutic agent according to Example 56, wherein the bioactive glass comprises bioactive glass particles with a size of 5-120 nm.
[0231] Example 63. The therapeutic agent according to Example 56, wherein the bioactive glass comprises a group of bioactive glass particles, most of which are between 5-120 nm in size.
[0232] Example 64. The therapeutic agent according to Example 56, wherein the bioactive glass comprises a group of 45S5 bioactive glass particles, wherein 90% of the particles are between 5-120 nm in size.
[0233] Example 65. The therapeutic agent according to Example 56, wherein the bioactive glass comprises a group of 45S5 bioactive glass particles, wherein 99% of the particles are between 5-120 nm in size.
[0234] Example 66. The therapeutic agent according to Example 56, wherein the bioactive glass comprises a group of 45S5 bioactive glass particles consisting essentially of 45S5 bioactive glass particles with a size of 5-120 nm.
[0235] Example 67. The therapeutic agent according to Example 56, wherein the bioactive glass comprises a group of 45S5 bioactive glass particles consisting of 45S5 bioactive glass particles with a size of 5-120 nm.
[0236] Example 68. The therapeutic agent according to Example 57, wherein the bioactive glass comprises bioactive glass particles with a size of 5-120 nm.
[0237] Example 69. The therapeutic agent according to Example 57, wherein the bioactive glass comprises a group of bioactive glass particles, most of which are between 5-120 nm in size.
[0238] Example 70. The therapeutic agent according to Example 57, wherein the bioactive glass comprises a group of 45S5 bioactive glass particles, wherein 90% of the particles are between 5-120 nm in size.
[0239] Example 71. The therapeutic agent according to Example 57, wherein the bioactive glass comprises a group of 45S5 bioactive glass particles, wherein 99% of the particles are between 5-120 nm in size.
[0240] Example 72. The therapeutic agent according to Example 57, wherein the bioactive glass comprises a group of 45S5 bioactive glass particles consisting essentially of 45S5 bioactive glass particles with a size of 5-120 nm.
[0241] Example 73. The therapeutic agent according to Example 57, wherein the bioactive glass comprises a group of 45S5 bioactive glass particles consisting of 45S5 bioactive glass particles with a size of 5-120 nm.
[0242] Example 74. The therapeutic agent according to Example 60, wherein the bioactive glass comprises bioactive glass particles with a size of 5-120 nm.
[0243] Example 75. The therapeutic agent according to Example 60, wherein the bioactive glass comprises a group of bioactive glass particles, most of which are between 5-120 nm in size.
[0244] Example 76. The therapeutic agent according to Example 60, wherein the bioactive glass comprises a group of 45S5 bioactive glass particles, wherein 90% of the particles are between 5-120 nm in size.
[0245] Example 77. The therapeutic agent according to Example 60, wherein the bioactive glass comprises a group of 45S5 bioactive glass particles, wherein 99% of the particles are between 5-120 nm in size.
[0246] Example 78. The therapeutic agent according to Example 60, wherein the bioactive glass comprises a group of 45S5 bioactive glass particles consisting essentially of 45S5 bioactive glass particles with a size of 5-120 nm.
[0247] Example 79. The therapeutic agent according to Example 61, wherein the bioactive glass comprises a group of 45S5 bioactive glass particles consisting of 45S5 bioactive glass particles with a size of 5-120 nm.
[0248] Example 80. The therapeutic agent according to Example 61, wherein the ratio of (NBG:GIC liquid) is between (1wt%:99wt%) and (5wt%:95wt%), including the endpoints.
[0249] Example 81. The therapeutic agent according to Example 61, wherein the (GIC) liquid comprises water and NGIC powder.
[0250] Example 82. The therapeutic agent according to Example 61, wherein the (GIC) liquid is substantially composed of water and NGIC powder.
[0251] Example 83. The therapeutic agent according to Example 61, wherein the (GIC) liquid is composed of water and NGIC powder.
[0252] Example 84. The therapeutic agent according to Example 81, wherein the NGIC powder comprises:
[0253]
[0254]
[0255] Example 85. The therapeutic agent according to Example 81, wherein the NGIC powder comprises:
[0256]
[0257] Example 86. The therapeutic agent according to Example 81, wherein the NGIC powder comprises:
[0258]
[0259] Example 87. The therapeutic agent according to Example 81, wherein the NGIC liquid comprises:
[0260] 45wt% water;
[0261] 36wt% polyacrylic acid;
[0262] 9 wt% polycarboxylic acids; and
[0263] 10wt% poly(vinylphosphonic acid).
[0264] Example 88. The therapeutic agent according to Example 86, wherein the NGIC liquid comprises:
[0265] 45wt% water;
[0266] 36wt% polyacrylic acid;
[0267] 9 wt% polycarboxylic acids; and
[0268] 10wt% poly(vinylphosphonic acid).
[0269] Materials and Methods
[0270] All patents, patent applications, provisional applications and publications mentioned or cited herein are incorporated herein by full reference to the extent that they are not inconsistent with the express teachings and definitions herein, including all figures and tables.
[0271] The following are examples demonstrating the procedures for practicing this invention. These examples should not be construed as limiting. Unless otherwise stated, all percentages are by weight and all solvent mixture proportions are by volume.
[0272] Example 1— Figure 1 and 2 Preparation of test samples
[0273] Materials: NGIC samples were prepared by manual mixing for biocompatibility and mechanical strength analysis.
[0274] Methods: NGIC materials were prepared by adding different proportions of poly(vinylphosphonic acid) (PVPA) (containing 1 wt%, 5 wt%, 10 wt%, and 20 wt% PVPA) to a polyacrylic acid solution. Silicate glass powder was mixed with the polyacrylic acid solution at a powder / liquid ratio of 3.6 / 1.0 for 60 seconds at 23°C and humidity greater than 30% and less than 70%. Conventional GIC without PVPA was used as a control. Six samples were prepared for each subgroup.
[0275] Data: 144 circular samples with a diameter of 5 mm and a height of 2 mm were prepared to evaluate cytotoxicity (ISO 7405:2018). 60 samples with a diameter of 4 mm and a height of 6 mm were prepared to evaluate mechanical strength according to ISO standard (ISO 9917-1:2007).
[0276] Analysis: For a common standard deviation of 10 with a power of 0.80 and α = 0.05, the sample size for each subgroup is six.
[0277] Results: 204 NGIC material samples were generated for each test group according to Table 2.
[0278] Table 2. Figure 1-2 The composition of the materials provided
[0279]
[0280] Example 2—Biocompatibility
[0281] Materials: 144 circular samples from Example 1 were plated in 96-well plates for testing with Cell Counting Kit-8.
[0282] Methods: Circular samples with a diameter of 5 mm and a height of 2 mm were prepared to assess cytotoxicity (ISO 7405:2018). Samples were sterilized using an ethylene oxide sterilizer. Human gingival fibroblasts (HGF) were cultured on the sample surface in Dulbecco's Modified Eagle's Medium (DMEM) supplemented with 10% fetal bovine serum, 60 μg / mL penicillin, and 100 μg / mL streptomycin in an incubator at 37°C with 5% carbon dioxide and humidified air. The cytotoxicity of AbGIC was determined by qualitative and quantitative assessment of the cells (ISO 10993-5:2009). The proliferative potential of HGF was determined by the Cell Count Kit-8 (CCK-8) assay (Apexbio, MA, USA). For the CCK-8 assay, 3 × 10⁶ cells were cultured on the sample surface. 3 HGF cells were seeded onto the sample surface of a 96-well plate. After co-culturing for 1, 3, 5, and 7 days, the HGF cells were treated with CCK-8 reagent at 37°C for 2 hours, and the optical density (OD) at 450 nm was measured using a microplate reader Spectramax M2 (Molecular Devices, USA).
[0283] Data: For CCK-8 assays, the optical density (OD) of HGF cells at 450 nm was lower in the NGIC group compared to the blank control group without NGIC samples (P<0.01). However, there was no statistically significant difference between the PVPA-added group and the commercial group in NGIC (P>0.05).
[0284] Analysis: Qualitative data were analyzed using SPSS Statistics 20 (IBM Corporation, Somers, NY, USA). Quantitative data are expressed as mean ± standard deviation. One-way ANOVA was used to determine differences between groups. The cutoff value was set at 5% significance.
[0285] Result: As Figure 1 As shown, the addition of PVPA to NGIC demonstrated similar biocompatibility to commercial GIC products of the relevant technology in biocompatibility and toxicity tests.
[0286] Example 3—Mechanical Strength
[0287] Materials: Sixty samples from Example 1 were mounted on an Instron testing machine to determine compressive strength and radial tensile strength.
[0288] Methods: Cylindrical samples were prepared by inserting freshly mixed cement paste into cylindrical polyethylene molds with a diameter of 4 mm and a height of 6 mm, according to ISO standard (ISO 9917-1:2007). After static loading under a glass slide for 60 minutes, the samples were removed from the molds and covered with a thin layer of petroleum jelly. After 24 hours, the petroleum jelly was removed, and the compressive strength and radial tensile strength (DTS) were determined using a mechanical testing apparatus (ELECTROPULS E3000 universal testing system, INSTRON, MA, USA). The compressive strength (MPa) was calculated using the following equation:
[0289]
[0290] Where L is the fracture load and D is the sample diameter.
[0291] DTS (MPa) is calculated using the following formula:
[0292]
[0293] Where L is the fracture load (N), D is the sample diameter, and H is the sample height.
[0294] Data: For compressive strength, NGIC containing 10% PVPA showed increased compressive strength compared to the control group (P<0.05). However, NGIC containing 20% PVPA showed decreased compressive strength compared to the control group (P<0.05). There was no difference in compressive strength between NGIC containing 1% and 5% PVPA compared to the control group (P>0.05).
[0295] Regarding radial tensile strength, NGIC containing 10% PVPA showed an increased radial tensile strength compared to the control group (P<0.05). However, NGIC containing 20% PVPA showed a decreased radial tensile strength compared to the control group (P<0.05). There was no difference in radial tensile strength between NGIC containing 1% and 5% PVPA compared to the control group (P>0.05).
[0296] Analysis: Qualitative data were analyzed using SPSS Statistics 20 (IBM, Summers, New York). Quantitative data are expressed as mean ± standard deviation. One-way ANOVA was used to determine differences between groups. The cutoff value was set at 5% significance.
[0297] Result: As Figure 2 As shown, adding 10% PVPA can improve the mechanical strength of NGIC in both compressive strength and radial tensile strength tests.
[0298] Example 4— Figure 3 Preparation of test samples
[0299] Materials: Nano-silver bioactive glass was synthesized via a sol-gel method for SEM and EDX analysis.
[0300] Methods: 1. Prepare 5g of 45S5 bioactive glass. Add 7.31g of TEOS to 1M nitric acid, where the molar ratio of H2O:TEOS = 18:1. Nitric acid is prepared by mixing 1.7ml of 69% nitric acid with 25ml of DI water. Stir the mixture for 2 hours until a clear sol is formed. Add 0.77g of TEP. Then add 5.17g of Ca(NO3)2. Add 3.375g of NaNO3. Finally, add 0.415g of AgNO3. Stir the mixture until all chemicals are dissolved. Place the sol mixture in a microwave oven and irradiate at 800W for 15 minutes. Dry the mixture at 80°C overnight. Calcinate the dried gel at 700°C for 3 hours. Grind the collected solid to obtain a fine powder.
[0301] 45S5 bioactive glass = Ag:SiO2:Na2O:CaO:P2O5 = 3:43.1:24.4:26.9:2.6 (molar ratio)
[0302]
[0303] Table 3.45S5 Bioactive Glass Compositions.
[0304] Results: 5g of 45S5 bioactive glass powder was used for SEM and EDX analysis.
[0305] Example 5—SEM and EDX
[0306] Materials: A 0.1 g sample from Example 4 was observed under scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) under SEM.
[0307] Methods: The surface morphology of 45S5 bioactive glass powder was observed under a scanning electron microscope (SEM) (Hitachi S-4800FEG, Hitachi Ltd., Tokyo, Japan) in a 5 kV high vacuum mode. Elemental analysis was performed on the surface of six samples in each group. Ion levels were assessed by energy-dispersive X-ray spectroscopy (EDX) under SEM. Five 5 × 5 μm samples were measured on the enamel surface of each sample. 2 Element evaluation is performed on a square region.
[0308] Data: SEM micrographs confirmed that the bioactive glass is composed of nanoparticles with irregular shapes. EDX confirmed the presence of Ag, Si, Na, Ca, and P in the prepared glass sample.
[0309] Result: As Figure 3 As shown, embodiments of the present invention provide a novel nano-silver bioactive glass (NanoAgBAG).
[0310] Example 6— Figures 4 to 9 Preparation of test samples
[0311] Materials: NGIC samples were prepared by manual mixing for biocompatibility and mechanical strength analysis, fluoride ion release analysis, and calcium, phosphate and silver release analysis.
[0312] Methods: NGIC materials were prepared by incorporating different proportions of NanoAg BAG (containing 0%, 1%, 2%, and 5% by weight of NanoAg BAG) into silicate glass powder. The silicate glass powder was mixed with polyacrylic acid containing 10% poly(vinylphosphonic acid) (PVPA) at a powder / liquid ratio of 3.6 / 1.0 for 60 seconds at 23°C and humidity greater than 30% and less than 70%. Conventional GIC without PVPA and NanoAg BAG served as a control. Six samples were prepared for each subgroup.
[0313] Data: 144 circular samples with a diameter of 5 mm and a height of 2 mm were prepared to assess cytotoxicity (ISO 7405:2018). 60 samples with a diameter of 4 mm and a height of 6 mm were prepared to assess mechanical strength according to ISO standard (ISO 9917-1:2007). 30 circular samples with a diameter of 5 mm and a height of 2 mm were prepared to assess fluoride ion release. 30 circular samples with a diameter of 5 mm and a height of 2 mm were prepared to assess the release of calcium, phosphate, and silver.
[0314] Analysis: For a common standard deviation of 10 with a power of 0.80 and α = 0.05, the sample size for each group is six.
[0315] Results: 264 circular NGIC material samples were generated for each test group according to Table 4.
[0316] Table 4. Figure 4-11 The composition of the materials provided
[0317]
[0318] Example 7—Biocompatibility
[0319] Materials: 144 samples from Example 6 were plated in 96-well plates for testing with Cell Counting Kit-8.
[0320] Methods: Circular samples with a diameter of 5 mm and a height of 2 mm were prepared to assess cytotoxicity (ISO 7405:2018). Samples were sterilized using an ethylene oxide sterilizer. Human gingival fibroblasts (HGF) were cultured on the sample surface in Duchenne Modified Ehrlich Medium (DMEM) supplemented with 10% fetal bovine serum, 60 μg / mL penicillin, and 100 μg / mL streptomycin at 37°C in an incubator with 5% carbon dioxide and humidified air. The cytotoxicity of NGIC was determined by qualitative and quantitative assessment of the cells (ISO 10993-5:2009). The proliferative potential of HGF was determined by the Cell Count Kit-8 (CCK-8) assay (Apexbio, Massachusetts, USA). For the CCK-8 assay, 3 × 10⁶ cells were cultured. 3 HGF cells were seeded onto the sample surface of a 96-well plate. After co-culturing for 1, 3, 5, and 7 days, the HGF cells were treated with CCK-8 reagent at 37°C for 2 hours, and the optical density (OD) at 450 nm was measured using a microplate reader, Spectramax M2 (Molecular Devices, Inc., USA).
[0321] Data: For CCK-8 assays, the optical density (OD) of HGF cells at 450 nm was shown to be lower in the NGIC group compared to the blank control group without NGIC samples (P<0.01). However, there was no statistically significant difference between the NGIC NanoAg BAG and PVPA-added groups and the commercial group (0% NanoAg BAG + 0% PVPA) (P>0.05).
[0322] Analysis: Qualitative data were analyzed using SPSS Statistics 20 (IBM, Summers, New York). Quantitative data are expressed as mean ± standard deviation. One-way ANOVA was used to determine differences between groups. The cutoff value was set at 5% significance.
[0323] Result: As Figure 4 As shown, the addition of NanoAg BAG and PVPA exhibited similar biocompatibility over 24 hours to the related technology GIC product (0% NanoAg BAG + 0% PVPA). The biocompatibility of 1% NanoAg BAG and 10% PVPA was also similar to that of the related technology GIC product.
[0324] Example 8—Mechanical Strength
[0325] Materials: Sixty samples from Example 6 were mounted on an Instron testing machine to determine compressive strength and radial tensile strength.
[0326] Methods: Cylindrical samples were prepared by inserting freshly mixed cement paste into cylindrical polyethylene molds with a diameter of 4 mm and a height of 6 mm, according to ISO standard (ISO 9917-1:2007). After static loading under a glass slide for 60 minutes, the samples were removed from the molds and covered with a thin layer of petroleum jelly. After 24 hours, the petroleum jelly was removed, and the compressive strength and radial tensile strength (DTS) were determined using a mechanical testing apparatus (ELECTROPULS E3000 universal testing system, INSTRON, MA, USA). The compressive strength (MPa) was calculated using the following equation:
[0327]
[0328] Where L is the fracture load and D is the sample diameter.
[0329] DTS (MPa) is calculated using the following formula:
[0330]
[0331] Where L is the fracture load (N), D is the sample diameter, and H is the sample height.
[0332] Data: For compressive strength, the addition of 1% NanoAg BAG + 10% PVPA showed the highest compressive strength among all groups, and also showed higher compressive strength than the commercial group (0% NanoAg BAG + 0% PVPA) (P < 0.01). The addition of 0% NanoAg BAG + 10% PVPA and 2% NanoAg BAG + 10% PVPA showed higher compressive strength than the commercial group (0% NanoAg BAG + 0% PVPA) (P < 0.01). The addition of 5% NanoAg BAG + 10% PVPA showed no statistically significant difference in compressive strength compared to the commercial group (0% NanoAg BAG + 0% PVPA) (P > 0.05).
[0333] For radial tensile strength, the addition of 1% NanoAg BAG + 10% PVPA showed the highest radial tensile strength among all groups, and also showed higher radial tensile strength than the commercial group (0% NanoAg BAG + 0% PVPA) (P < 0.01). The addition of 0% NanoAg BAG + 10% PVPA and 2% NanoAg BAG + 10% PVPA showed radial tensile strength higher than the commercial group (0% NanoAg BAG + 0% PVPA) (P < 0.01). The addition of 5% NanoAg BAG + 10% PVPA showed no statistically significant difference in radial tensile strength compared to the commercial group (0% NanoAg BAG + 0% PVPA) (P > 0.05).
[0334] Analysis: Qualitative data were analyzed using SPSS Statistics 20 (IBM, Summers, New York). Quantitative data are expressed as mean ± standard deviation. One-way ANOVA was used to determine differences between groups. The cutoff value was set at 5% significance.
[0335] Result: As Figure 5 As shown, the addition of 1% NanoAg BAG + 10% PVPA can improve the mechanical strength of NGIC in both compressive strength and radial tensile strength tests.
[0336] Example 9—Fluoride Ion Release
[0337] Materials: Thirty circular samples from Example 6 were stored in a 24-well plate for fluoride ion release testing.
[0338] Methods: Thirty disc-shaped samples, 5 mm in diameter and 2 mm thick, were used. Fluoride ion release was recorded for 14 days. Each sample was immersed in a capped polystyrene bottle containing 2 mL of distilled water (pH 7.0). The samples were stored at 37°C for a total immersion time of 14 days. Fluoride ion concentrations in the storage solution were measured at different intervals using a fluoride ion selective electrode (Oakton, Cole Parmer, IL, USA) connected to an ion analyzer (Oakton 510 ion series). The electrode was calibrated to external standards of 0.1, 1, 10, 100, and 1000 μg / g F. Before measuring fluoride ions, 2 mL of total ionic strength adjustment buffer TISAB II (Thermo Fisher Scientific, Chelmsford, USA) was added to the storage solution to increase the ionic strength in the storage solution and thus improve the accuracy of the readings. If any potential drift is found in the electrode measurements, the electrodes are recalibrated using standards. The coefficient of determination for all calibrations is >0.99. Standard curves are plotted against standards with automatically determined mV potentials, which are further used to derive the F concentration in the test solution.
[0339] Data: The fluoride ion release level of the NGIC material was high on the first day. Subsequently, the daily fluoride ion release of the NGIC material gradually decreased until day 7, and remained at a stable low level from day 7 to day 14. The NGIC material with 5% NanoAg BAG + 10% PVPA showed the highest fluoride ion release, significantly higher than the commercial group (0% NanoAg BAG + 0% PVPA) (P < 0.05). Subsequently, the NGIC groups with 1% NanoAg BAG + 10% PVPA and 2% NanoAg BAG + 10% PVPA showed significantly higher fluoride ion release than the commercial group (0% NanoAg BAG + 0% PVPA) (P < 0.05). The NGIC group with 0% NanoAg BAG + 10% PVPA showed the same fluoride ion release as the commercial group (0% NanoAg BAG + 0% PVPA) (P > 0.05).
[0340] Analysis: Qualitative data were analyzed using SPSS Statistics 20 (IBM, Summers, New York). Quantitative data are expressed as mean ± standard deviation. One-way ANOVA was used to determine differences between groups. The cutoff value was set at 5% significance.
[0341] Result: As Figure 6 As shown, compared with the related technology GIC, NGIC releases more fluoride ions, which can promote tooth remineralization and prevent, reduce or inhibit tooth decay.
[0342] Example 10—Release of phosphate, calcium, and silver
[0343] Materials: Thirty samples from Example 6 were stored in 15 mL test tubes for the release of calcium, phosphate, and silver.
[0344] Methods: Ag was detected using inductively coupled plasma optical emission spectrometry (ICP-OES) (Spectro arcos, Germany). A series of standard solutions were prepared from 1000 μg / mL national standard solutions of calcium, phosphate, and silver (GSB04-1712-2004, China), and standard curves for each metal element were then constructed by measuring them individually. Preparation of silver standard solutions: Different volumes of 1000 μg / mL silver standard stock solution were pipetted into volumetric flasks to dilute the standard solution into a series of different calcium, phosphate, and silver ion solutions with concentrations of 0, 100, 15, 625, 0.03, 125, 0.06, 25, 0.125, 0.25, 0.5, 1, and 5 mg / L. 4 mL of test solution was used for each sample. First, the sample introduced into the ICP-OES used in the experiment was rinsed in distilled water to clean the tubing. Then, the prepared calcium, phosphate, and silver ion standard solutions were extracted separately, and working curves for calcium, phosphate, and silver ions were plotted using the obtained data. Based on the experimental measurement results of the calcium, phosphate, and silver elemental standard solutions, standard curves were plotted from the ion content corresponding to the emission intensity. Linear fitting was then performed to finally obtain the regression equations and correlation coefficients for the calcium, phosphate, and silver elemental standard curves. Triple copies were used to estimate the calcium, phosphate, and silver concentrations of each test solution.
[0345] Data: For phosphate release, phosphate release was higher on the first 7 days (day 7) than on the second 7 days (day 14). During days 7 and 14, the NGIC group with 5% NanoAg BAG + 10% PVPA showed the highest phosphate release, significantly higher than the commercial group (0% NanoAg BAG + 0% PVPA) (P < 0.01). There was no statistically significant difference in phosphate release between the NGIC group with 0% NanoAg BAG + 10% PVPA, 1% NanoAg BAG + 10% PVPA, and 2% NanoAg BAG + 10% PVPA and the commercial group (0% NanoAg BAG + 0% PVPA) (P > 0.05).
[0346] Regarding calcium release, calcium release was higher on the first 7 days (day 7) than on the second 7 days (day 14). During days 7 and 14, the highest calcium release was observed with the addition of 5% NanoAg BAG + 10% PVPA, significantly higher than the commercial group (0% NanoAg BAG + 0% PVPA) (P < 0.01). No calcium release was detected in the NGIC groups with 0% NanoAg BAG + 10% PVPA, 1% NanoAg BAG + 10% PVPA, 2% NanoAg BAG + 10% PVPA, or the commercial group (0% NanoAg BAG + 0% PVPA).
[0347] Regarding silver release, calcium release was higher on the first 7 days (day 7) than on the second 7 days (day 14). During days 7 and 14, the highest calcium release was observed with the addition of 5% NanoAg BAG + 10% PVPA, significantly higher than the commercial group (0% NanoAg BAG + 0% PVPA) (P < 0.01). NGICs with the addition of 1% NanoAg BAG + 10% PVPA and 2% NanoAg BAG + 10% PVPA showed higher silver release than the commercial group (0% NanoAg BAG + 0% PVPA), with statistically significant differences (P < 0.01). No silver release was detected in NGICs with the addition of 0% NanoAg BAG + 10% PVPA and 1% NanoAg BAG + 10% PVPA.
[0348] Analysis: Qualitative data were analyzed using SPSS Statistics 20 (IBM, Summers, New York). Quantitative data are expressed as mean ± standard deviation. One-way ANOVA was used to determine differences between groups. The cutoff value was set at 5% significance.
[0349] Result: As Figure 7-8 As shown, NGIC releases calcium and phosphate, which can promote tooth remineralization and prevent, reduce, or inhibit tooth decay. Figure 9 As shown, NGIC releases a high concentration of silver on day 7, which can inhibit the growth of oral bacteria.
[0350] Example 11—Composition
[0351] Tables 5 and 6 provide exemplary compositions for one embodiment of the invention. The ratio of nanosilver bioactive glass (NBG) to NGIC in Table 6 includes compositions ranging from 1% NBG and 99% NGIC to 5% NBG and 95% NGIC. The NGIC powder component and the NGIC liquid component are mixed separately, and then the two are combined to form NGIC. NGIC and NBG are then combined to form a therapeutic composition for dental use.
[0352] Table 5. Composition of Nano-Silver Bioactive Glass (NBG)
[0353] <![CDATA[SiO2]]> 41.1% CaO 23.9% <![CDATA[Na2O]]> 24.0% <![CDATA[P2O5]]> 5.9% Ag nanoparticles 5.1%
[0354] Table 6. Composition of NGIC
[0355]
[0356]
[0357] Table 7. Composition of various components of NGIC
[0358]
[0359] Example 12—Properties
[0360] The compressive strength of the NGIC provided, measured according to embodiments of the present invention, is higher than the compressive strength values reported in related art. In addition to the increased strength, complementary benefits of certain embodiments of the present invention include, but are not limited to, the following aspects.
[0361] The GICs taught in related technologies have antibacterial effects against a limited number of bacteria (e.g., four different strains). In embodiments of the present invention, the release of silver ions from the NGICs was evaluated in deionized water for 7 and 14 days, demonstrating and contrasting a broad-spectrum antibacterial effect exceeding that reported in related technologies.
[0362] Bioactive glass GICs, as taught in related technologies, claim to have antibacterial effects. This is in some cases due to pH changes after immersion in physiological saline. In embodiments of the present invention, the antibacterial effect of NGICs is due to nano-silver, which advantageously provides an alternative mode of action for improving antibacterial efficacy.
[0363] Example 13— Figure 10 Preparation of test samples
[0364] Materials: NGIC samples were prepared by manual mixing for flexural strength analysis.
[0365] Methods: NGIC materials were prepared by incorporating different proportions of NanoAg BAG (containing 0%, 1%, 2%, and 5% by weight of NanoAg BAG) into silicate glass powder. The silicate glass powder was mixed with polyacrylic acid containing 10% poly(vinylphosphonic acid) (PVPA) at a powder / liquid ratio of 3.6 / 1.0 for 60 seconds at 23°C and humidity greater than 30% and less than 70%. Conventional GIC without PVPA and NanoAg BAG served as a control. Six samples were prepared for each subgroup.
[0366] Data: Thirty rectangular samples with a length of 25 mm and a thickness and width of 2 mm were prepared to evaluate the flexural strength according to ISO standard (ISO4049:2019).
[0367] Analysis: For a common standard deviation of 10 with a power of 0.80 and α = 0.05, the sample size for each subgroup is six.
[0368] Results: According to Table 4, 30 rectangular NGIC material samples were generated for each test group.
[0369] Example 14—Flexural Strength
[0370] Materials: Thirty samples from Example 13 were mounted on an Instron testing machine to determine flexural strength.
[0371] Method: Use a split stainless steel mold (25mm in length and 2mm in width and height).
[0372] Rectangular samples were prepared according to ISO standard (ISO 4049:2019). After static loading under a glass slide for 60 minutes, the samples were removed from the mold and covered with a thin layer of petroleum jelly. After 24 hours, the petroleum jelly was removed from the samples, and the flexural strength (FS) was determined using a mechanical testing apparatus (ELECTROPULS E3000 universal testing system, INSTRON, Norwood, Massachusetts, USA). The flexural strength (MPa) was calculated using the following equation:
[0373]
[0374] Where F is the load (force) (MPa) at the fracture point, L is the support span length, b is the width, and d is the sample thickness.
[0375] Data: For flexural strength, the addition of 1% NanoAg BAG + 10% PVPA showed the highest flexural strength among all groups, and also showed higher flexural strength than the commercial group (0% NanoAg BAG + 0% PVPA) (P < 0.05). The addition of 0% NanoAg BAG + 10% PVPA also showed higher flexural strength than the commercial group (0% NanoAg BAG + 0% PVPA) (P < 0.05). The addition of 2% NanoAg BAG + 10% PVPA and 5% NanoAg BAG + 10% PVPA showed no statistically significant difference in flexural strength compared to the commercial group (0% NanoAg BAG + 0% PVPA) (P > 0.05).
[0376] Analysis: Qualitative data were analyzed using SPSS Statistics 20 (IBM, Summers, New York). Quantitative data are expressed as mean ± standard deviation. One-way ANOVA was used to determine differences between groups. The cutoff value was set at 5% significance.
[0377] Result: As Figure 10 As shown, the addition of 0% NanoAg BAG + 10% PVPA and 1% NanoAg BAG + 10% PVPA enhances the flexural strength of NGIC.
[0378] Figure 10 Results of flexural strength in various material groups according to certain embodiments of the present invention are shown. (*p<0.01).
[0379] Example 15— Figure 11 Preparation of test samples
[0380] Materials: NGIC samples were prepared to test antibacterial efficacy using a biomembrane metabolic activity assay.
[0381] Methods: NGIC materials were prepared by incorporating different proportions of NanoAg BAG (containing 0%, 1%, 2%, and 5% by weight of NanoAg BAG) into silicate glass powder. The silicate glass powder was mixed with polyacrylic acid containing 10% poly(vinylphosphonic acid) (PVPA) at a powder / liquid ratio of 3.6 / 1.0 for 60 seconds at 23°C and humidity greater than 30% and less than 70%. Conventional GIC without PVPA and NanoAg BAG served as a control. Six samples were prepared for each subgroup.
[0382] Data: Thirty circular samples with a diameter of 5 mm and a height of 2 mm were prepared to evaluate the antimicrobial test.
[0383] Analysis: For a common standard deviation of 10 with a power of 0.80 and α = 0.05, the sample size for each group is six.
[0384] Results: According to Table 4, 30 circular NGIC material samples were generated for each test group.
[0385] Example 16—Absorbance and antibacterial test at 492 nm optical density (OD)—biomembrane metabolic activity
[0386] Materials: Thirty samples from Example 15 were immersed in Streptococcus mutans (S. mutans) culture for biofilm metabolic activity testing.
[0387] Methods: Circular samples were prepared using a Teflon mold (5 mm in diameter and 2 mm in height) to evaluate antibacterial efficacy. Streptococcus mutans, American Type Culture Collection (ATCC) UA159, was used in this study. Each sample was immersed in 1 mL of brain and heart infusion broth for 10 minutes. 7 The samples were incubated at 37°C for 2 days with Streptococcus mutans culture at 100 cells / mL. The metabolic activity of the Streptococcus mutans biofilm on the samples was assessed by XTT (2,3-(2-methoxy-4-nitro-5-thiophenyl)'5-[(phenylamino)carbonyl]□2H-tetrazole hydroxide) reduction assay (Sigma-Aldrich). After 2 days of incubation, 100 μL of XTT reagent solution (AppliChem GmbH, Darmstadt, Germany) was added to each well and incubated at 37°C for 3 hours. The solution was then collected and centrifuged at 13,200 rpm for 10 minutes to remove debris. The absorbance (OD) was then measured at 492 nm using a microplate reader.
[0388] Data: Biofilm metabolic activity assays showed that the absorbances of 0% NanoAg BAG+0% PVPA, 0% NanoAg BAG+10% PVPA, 1% NanoAg BAG+10% PVPA, 2% NanoAg BAG+10% PVPA, and 5% NanoAg BAG+10% PVPA were 0.42±0.04, 0.44±0.03, 0.33±0.05, 0.26±0.05, and 0.17±0.05, respectively. Biofilms on the surfaces of 1% NanoAg BAG+10% PVPA, 2% NanoAg BAG+10% PVPA, and 5% NanoAg BAG+10% PVPA exhibited lower metabolic activity than the commercial group (0% NanoAg BAG+0% PVPA) (P<0.05). Adding 0% NanoAg BAG + 10% PVPA showed no statistically significant difference in biofilm compared to the commercial group (0% NanoAg BAG + 0% PVPA) (P>0.05).
[0389] Analysis: Qualitative data were analyzed using SPSS Statistics 20 (IBM, Summers, New York). Quantitative data are expressed as mean ± standard deviation. One-way ANOVA was used to determine differences between groups. The cutoff value was set at 5% significance.
[0390] Result: As Figure 11As shown, the addition of 1% NanoAg BAG+10% PVPA, 2% NanoAg BAG+10% PVPA, and 5% NanoAg BAG+10% PVPA can reduce bacterial metabolic activity, thus demonstrating the enhanced antibacterial effect of NGIC.
[0391] It should be understood that the examples and embodiments described herein are for illustrative purposes only, and various modifications or variations will be suggested to those skilled in the art in light of this, and such modifications or variations will be included within the spirit and scope of this application and the appended claims. Furthermore, any element or limitation of any invention or embodiment thereof disclosed herein may be combined with any and / or all other elements or limitations disclosed herein (alone or in any combination) or any other invention or embodiment thereof, and all such combinations are contemplated to be within the scope of the invention, but not limited thereto.
[0392] All patents, patent applications, provisional applications and publications mentioned or cited herein are incorporated herein by full reference to the extent that they are not inconsistent with the express teachings and definitions herein, including all figures and tables.
[0393] As used herein, the singular forms “a / an” and “the” are intended to also include the plural forms, unless the context explicitly indicates otherwise. Furthermore, where the terms “including / include,” “having / has / with,” or variations thereof are used in the detailed description and / or claims, such terms are intended to be inclusive in a manner similar to the term “comprising.” Transitional terms / phrases (and any grammatical variations thereof) “comprising,” “comprises,” and “comprise” are used interchangeably; “consisting essentially of” and “consistsessentially of” are used interchangeably; and “consisting” and “consists” are used interchangeably.
[0394] The transitional terms "comprising," "comprises," or "comprise" are inclusive or open-ended and do not exclude additional unlisted elements or method steps. In contrast, the transitional phrase "consisting of" excludes elements, steps, or ingredients not specified in the claims. The phrases "consisting of" or "substantially consisting of" indicate that the claims cover embodiments containing the specified materials or steps, as well as those embodiments that do not substantially affect the fundamental and novel characteristics of the claims. The use of the term "comprising" contemplates other embodiments "consisting of" or "substantially consisting of" the components.
[0395] When this document uses the term "scope," such as for dose range, combination, and sub-combination of ranges (e.g., sub-ranges within the scope of disclosure), it is intended to identify the specific embodiments included therein.
[0396] The terms “about” or “approximately” mean within an acceptable margin of error for a particular value as determined by one of ordinary skill in the art, which will depend in part on how the value was measured or determined, i.e., the limitations of the measurement system. For example, “about” may mean within one or more standard deviations according to practice in the art. Alternatively, “about” may mean a range of up to 0-20%, 0 to 10%, 0 to 5%, or up to 1% of a given value. When a particular value is described in this application and claims, unless otherwise indicated, it should be assumed that the term “about” means that the particular value is within an acceptable margin of error. In the context of compositions containing amounts of component concentrations where the term “about” is used, these values include a variation (error range) of 0-10% around the value (X ± 10%).
[0397] As used in this document, each of n, N, X, and Y is intended to contain ≥1, ≥2, ≥3, ≥4, ≥5, ≥6, ≥7, ≥8, ≥9, ≥10, ≥11, ≥12, ≥13, ≥14, ≥15, ≥16, ≥17, ≥18, ≥19, ≥20, ≥21, ≥22, ≥23, ≥24, ≥25, ≥26, ≥27, ≥28, ≥29, and ≥30.
[0398] Unless otherwise defined, all technical terms, symbols, and other scientific terms or proprietary terms used herein are intended to have the meaning commonly understood by one of ordinary skill in the art to which this invention pertains. In some instances, for clarity and / or ease of reference, terms having a commonly understood meaning are defined herein, and the inclusion of such definitions herein should not necessarily be construed as representing a material difference from the meaning commonly understood in the art. It should be further understood that terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning as otherwise defined in the relevant field and / or herein.
[0399] References
[0400] 1. Hoshika, S. et al., Effect of conditioning and 1-year aging on the bond strength and interfacial morphology of glass-ionomer cement bonded to dentin. Dental Materials, 2021, 37(1): 106-112.
[0401] 2. Agha, A., S. Parker and MP Patel, Development of experimental resin modified glass-ionomer cements (RMGICs) with reduced water uptake and dimensional change. Dental Materials, 2016, 32(6): 713-22.
[0402] 3. Friedl, K., KAHiller and KHF Friedl, Clinical performance of a new glass-ionomer based restoration system: a retrospective cohort study. Dental Materials, 2011, 27(10): 1031-7.
[0403] 4. Gemeinhart, RA et al., Osteoblast-like cell attachment to and calcification of novel phosphonate-containing polymeric substrates. Journal of Biomedical Materials Research Part A: An Official Journal of The Society for Biomaterials, The Japanese Society for Biomaterials, and The Australian Society for Biomaterials and the Korean Society for Biomaterials, 2006, 78(3): 433-440.
[0404] 5. Heck, K. et al., Six-year results of a randomized controlled clinical trial of two glass-ionomer cements in class II cavities. Journal of Dentistry, 2020, 97: 103333.
[0405] 6. Espinosa-Cristóbal, LF et al., Antimicrobial and Substantivity Properties of Silver Nanoparticles against Oral Microbiomes Clinically Isolated from Young and Young-Adult Patients. Journal of Nanomaterials, 2019: 3205971.
[0406] 7. Nizami, MZI et al., Metal and Metal Oxide Nanoparticles in Caries Prevention: A Review. Nanomaterials (Basel), 2021.11(12).
[0407] 8. Hench, LL, 《 The story of ). Journal of Materials Science: Materials in Medicine, 2006, 17(11): 967-978.
[0408] 9. Banerjee, A. et al., An in vitro evaluation of selective demineralized enamel removal using bio-active glass air abrasion. Clinical Oral Investigations, 2011, 15(6): 895-900.
[0409] 10. Yang, SY et al., Acid neutralizing, mechanical and physical properties of pit and fissure sealants containing melt-derived 45S5 bioactive glass. Dental Materials, 2013, 29(12): 1228-35.
Claims
1. A glass ionomer cement, characterized in that, It includes: Silicate glass powder, including calcium aluminofluorosilicate glass; Polyacrylic acid powder; Poly(vinylphosphonic acid) PVPA powder; Nano-silver bioactive glass; as well as Polyacrylic acid solution; The glass ionomer cement is a powder-liquid two-phase system, wherein the powder phase comprises silicate glass powder, polyacrylic acid powder and nano-silver bioactive glass, and the liquid phase comprises polyacrylic acid solution and poly(vinylphosphonic acid) powder. In the liquid phase, the wt% ratio of (polyacrylic acid) / PVPA is equal to 90 / 10; The wt% ratio of (silicate glass powder) / (nano-silver bioactive glass) is greater than or equal to 95 / 5, and the nano-silver bioactive glass is obtained by incorporating nano-silver into bioactive glass.
2. The glass ionomer cement according to claim 1, characterized in that, The silicate glass powder is calcium aluminum fluoride silicate glass.
3. The glass ionomer cement according to claim 1, characterized in that, The wt% ratio of (silicate glass powder) / (nano silver bioactive glass) is greater than 98 / 2.
4. The glass ionomer cement according to claim 3, characterized in that, The wt% ratio of (silicate glass powder) / (nano silver bioactive glass) is greater than 99 / 1.
5. The glass ionomer cement according to claim 1, characterized in that, The wt% ratio of (silicate glass powder) / (nano silver bioactive glass) is greater than 95 / 5 but less than or equal to 99 / 1.
6. The glass ionomer cement according to claim 1, characterized in that, The nano-silver bioactive glass comprises a group of nano-silver particles, wherein the size of the particles in the nano-silver particle group is between 8 and 15 nm.
7. The glass ionomer cement according to claim 1, characterized in that, The nano-silver bioactive glass comprises a group of bioactive glass particles, wherein the size of the particles in the group of bioactive glass particles is between 5 and 120 nm.
8. As described in claim 6, characterized in that, The nano-silver bioactive glass comprises a group of bioactive glass particles, wherein the size of the particles in the group of bioactive glass particles is between 5 and 120 nm.
9. A method for preparing the glass ionomer cement as described in claim 1, characterized in that, The method involves mixing a liquid mixture of polyacrylic acid and PVPA with a powdered mixture of silicate glass powder, polyacrylic acid powder, and nano-silver bioactive glass.
10. The method according to claim 9, characterized in that, The silicate glass powder is calcium aluminum fluoride silicate glass.
11. The method according to claim 9, characterized in that, The wt% ratio of (silicate glass powder) to (nano-silver bioactive glass) is greater than or equal to 95 / 5, but less than or equal to 99 / 1.
Citation Information
Patent Citations
Glass compositions as an antimicrobial additive for dental materials
US20070122356A1
Dental glass ionomer cement composition
US20210212906A1
Poly(vinylphosphonic acid) glass ionomer cement
US5179135A
Treatment and prevention of dental pathology in humans and non-human animals
US9211246B2
Cement compositions
GB2291060A